2003
DOI: 10.1080/09638280310001608609
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use self report in chronic back pain—relationships to psychosocial factors, function performance, and medication use

Abstract: This first assessment of the relationship of alcohol consumption with back pain disability suggests that women with chronic back pain disability seldom report heavy alcohol consumption. Men with back pain disability who consume large amounts of alcohol have less physical disability despite similar pain. Despite potential interactions, heavy drinkers with pain do not use fewer narcotic analgesics than light drinkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 39 publications
3
15
1
Order By: Relevance
“…Recent studies have indicated that while health care providers are aware of the contraindications between alcohol and drugs, health outcomes are not regularly assessed(7). A study of patients attending a pain rehabilitation clinic found no difference in narcotic analgesic use between heavy and light drinkers(10), which suggests health care providers and/or patients pay insufficient attention to manufacturer’s warnings against mixing alcohol and narcotics. These findings serve to alert clinicians to assess for alcohol use in patients being treated for pain and to provide education about the problems associated with mixing alcohol with pain medications.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that while health care providers are aware of the contraindications between alcohol and drugs, health outcomes are not regularly assessed(7). A study of patients attending a pain rehabilitation clinic found no difference in narcotic analgesic use between heavy and light drinkers(10), which suggests health care providers and/or patients pay insufficient attention to manufacturer’s warnings against mixing alcohol and narcotics. These findings serve to alert clinicians to assess for alcohol use in patients being treated for pain and to provide education about the problems associated with mixing alcohol with pain medications.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been observed among patients with rheumatoid arthritis (Kondo et al, 2007) and chronic back pain (Gorman et al, 1987), and one study observed slightly lower pain intensity ratings among alcohol users (vs. nonusers) following traumatic injury (Rivara et al, 2008). Finally, in one study of patients referred for chronic back pain assessment, males who reported drinking 12 or more drinks per week performed better on tests of physical functioning, relative to lighter drinking and abstinent patients (Booker, Haig, Geisser, & Yamakawa, 2003). However, given that alcohol consumption was reported as a categorical variable, it is not possible to know whether some of the participants in that study drank at levels above the cut point for moderate drinking (i.e., > 14 drinks/week for adult males; USDHHS, 2010).…”
Section: Effects Of Alcohol On Painmentioning
confidence: 99%
“…First, fear-avoidance models of chronic pain posit that pain-related fear (e.g., fear of movement, re-injury, or pain) is an important psychological factor associated with the development and course of chronic pain conditions (Leeuw et al, 2007), and meta-analytic estimates indicate a robust association between pain-related fear and disability outcomes (Zale, Lange, Fields, & Ditre, 2013). One possibility is that as alcohol consumption facilitates disinhibition, the salience of fear-avoidance mechanisms may be reduced, which could, in turn, enhance pain-related functioning (Booker et al, 2003). There is also reason to believe that observations of improved quality of life and reduced disability may be related to social integration and stress-relieving effects of alcohol.…”
Section: Effects Of Alcohol On Painmentioning
confidence: 99%
“…Similar studies of proximal risks such as dependence severity, emotional distress, and social support and recovery resources provide further support for proximal risks’ potential role in increasing or decreasing the probability of relapse to problematic alcohol use (e.g., Garland, Franken, & Howard, 2012; Moos & Moos, 2006; Witkiewitz & Villarroel, 2009; Witkiewitz, 2011). Despite the identification of multiple risk factors, very few studies—and few theoretical models—have acknowledged the common experience of physical pain and pain interference as potential predictors of alcohol treatment outcomes (Booker, Haig, Geisser, & Yamakawa, 2003; Witkiewitz, Vowles, McCallion, Frohe, Kirouac, & Maisto, in press). This gap in the literature is surprising given evidence supporting the relationship between pain and negative affect (e.g., Davis, Zautra, & Smith, 2004), as well as the association between negative affect and alcohol use (Witkiewitz & Villarroel, 2009).…”
Section: Introductionmentioning
confidence: 99%